Impact of FED Interest Rate and Inflation Rate on Indonesian Sharia Stock Index: Moderating Role of Bank Indonesia's Interest Rate - Azis R, Abdul; Utami, Ayu Putri; Karim, Sitti Aminah Hamzah; Andriani, Nini (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study aims to analyze the effect of The FED interest rate on ISSI, analyze the effect of the inflation rate on ISSI, and test the role of BI Rate moderation in the relationship. The approach applied in this study is quantitative, with descriptive analysis to describe data characteristics and model testing using the Smart PLS application to answer the hypothesis. This study uses secondary data in the form of monthly data covering the Indonesian Sharia Stock Index (ISSI) obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id), The FED interest rate accessed via www.investing.com, and Inflation and BI Rate data taken from the Bank Indonesia website (www.bi.go.id), with a time span from 2014 to 2023. The results of the study indicate that The FED interest rate has a significant positive effect on the Indonesian Sharia Stock Index (ISSI). However, the BI Rate failed to moderate this effect. Inflation also showed a significant positive effect on ISSI, but the BI Rate was unable to moderate the effect of Inflation on ISSI. In addition, the BI Rate has been shown to have a significant negative impact on ISSI, where an increase in the BI Rate tends to reduce the attractiveness of sharia stocks.